Inclusive education in elementary school: possibilities of the experience of “being together” (Revista Contexto & Educação, 2026)
The article discusses the process of including children with disabilities in elementary education, considering the principles of inclusive education, the challenges faced, and strategies to promote inclusive environments in schools. The research was conducted through observations in an elementary school classroom at a state school in the Lages region (SC) and an interview with the classroom's lead teacher. Documentary analysis and a narrative literature review were also performed, selecting works aligned with a post-structuralist framework, specifically adopting Michel Foucault’s discourse analysis, which provides the foundation for the discussions and analyses. The study addresses the possibilities of constructing an inclusive formative experience that represents an encounter with the other, a “being together”, a concept based on Carlos Skliar that transcends physical presence to denote a coexistence of mutual affectivity and the negotiation of differences, which necessarily impacts all subjects. One of the main obstacles to inclusive schooling, as identified in the research, is the inadequacy of the educational project itself to accommodate all subjects, who no longer fit the mold of the project that produced the modern school. Results indicate that many schools are not prepared to meet the specific needs of students with disabilities, whether due to a lack of accessible physical infrastructure, a lack of teacher training, or, most gravely, the absence of an institutional project that places inclusion at the core of the educational process.
Keywords: Elementary School; Inclusive Education; People with Disabilities; Discourse Analysis; “Being together”